Neuropathological findings in essential tremor - Ioannis Mavroudis; Foivos Petridis (Folia Neuropathologica)
Essential tremor (ET) is one of the most common neurological conditions and the most common movement disorder. The pathophysiological mechanisms that underlie this entity have not yet been described. However, recent post-mortem brain studies have provided useful insight into the underlying pathology of ET. Two brain areas have been consistently found to present neuropathological alterations in patients with ET: the brainstem, for presence of Lewy bodies or neuronal depletion, and the cerebellum, regarding Purkinje cells’ morphology and density. In the present study we aim to review the literature on the main neuropathological findings in ET brains.